Famila: valores y juventud - Osorio, María Cristina (Revista Chilena de Humanidades, 2016)
Prof. Osorio’s studv reminds us of the central position of the family in the ethical web of society. The great relevance of the socialization process is inclicated, in particular as it affects the young through their perception, search for and selection of values. Sorne of her observations are supportecl by material found in the Acts of the First Congress on Social ancl Medico-Social Investigaban of Youth Problems, helcl in Santiago in 1986, where the aim was to deFine the identity as well as the actualization of the sexual role among the young. Thus, such values as those which control the practice of sexuality assume special significance where family patterns, education ancl religious preceptive may be decisive.